MANAJEMEN PEMBINAAN MENTAL ROHANI ISLAM PRAJURIT DI MARKAS KODAM II/SRIWIJAYA - Dul Munib (Conciencia, 2016)
The study was a qualitative research on the guidance management of Islamic spiritual mental of soldiers in the Military Command Headquarters II / Sriwijaya. This study examined about the mental guidance activities that consisted of the spiritual aspect, ideology and struggle that was restricted guidance activities of Islamic spiritual mental. With the formulation of the problem of how management from planning, organizing management, execution management was and how management of monitoring of guidance activities of Islamic spiritual mental for soldiers in the Military Command Headquarters II/ Sriwijaya was. The purpose of the study was to examine and analyze the management of planning, organizing, and implemention and to know monitoring management from the guidance of Islamic spiritual mental of soldiers. Type of the research was a qualitative field research with the sources of primary data and secondary data. Based on the analysis results that the guidance management of Islamic spiritual mental of soldiers in the Military Command Headquarters II / Sriwijaya run well, because the scope of management, from planning, organizing, implementing, and monitoring was already running well, although there was a shortage and barriers. Overall management was already running well; because the implementation of guidance management of Islamic spiritual mental of soldiers was categorized good enough, marked more increasing soldiers implement various activities of Islamic spiritual. This could suppress member violations, the indicator was personnel soldier increasingly enthusiastic learning about religion, rising prayers during hours of duty and active in other spiritual activities.